Rac and Cdc42 inhibitors reduce macrophage function in breast cancer preclinical models - Torres-Sanchez, Anamaris; Rivera-Robles, Michael; Castillo-Pichardo, Linette; Martínez-Ferrer, Magaly; Dorta-Estremera, Stephanie M.; Dharmawardhane, Suranganie (Frontiers in Oncology, 2023)
Metastatic disease lacks effective treatments and remains the primary cause of mortality from epithelial cancers, especially breast cancer. The metastatic cascade involves cancer cell migration and invasion and modulation of the tumor microenvironment (TME). A viable anti-metastasis strategy is to simultaneously target the migration of cancer cells and the tumor-infiltrating immunosuppressive inflammatory cells such as activated macrophages, neutrophils, and myeloid-derived suppressor cells (MDSC). The Rho GTPases Rac and Cdc42 are ideal molecular targets that regulate both cancer cell and immune cell migration, as well as their crosstalk signaling at the TME. Therefore, we tested the hypothesis that Rac and Cdc42 inhibitors target immunosuppressive immune cells, in addition to cancer cells. Our published data demonstrate that the Vav/Rac inhibitor EHop-016 and the Rac/Cdc42 guanine nucleotide association inhibitor MBQ-167 reduce mammary tumor growth and prevent breast cancer metastasis from pre-clinical mouse models without toxic effects. The potential of Rac/Cdc42 inhibitors to target macrophages was tested in human and mouse macrophage cell lines, where EHop-016 and MBQ-167 inhibited Rac and Cdc42 activation, actin cytoskeletal extensions, migration, and phagocytosis without affecting macrophage cell viability. Rac/Cdc42 inhibitors also reduced tumor- infiltrating macrophages and neutrophils in tumors of mice treated with EHop-016, and macrophages and MDSCs from spleens and tumors of mice with breast cancer, including activated macrophages and monocytes, following MBQ-167 treatment. Mice with breast tumors treated with EHop-016 significantly decreased the proinflammatory cytokine Interleukin-6 (IL-6) from plasma and the TME. This was confirmed from splenocytes treated with lipopolysaccharide (LPS) where EHop-016 or MBQ-167 reduced IL-6 secretion in response to LPS. Therefore, Rac/Cdc42 inhibition induces an antitumor environment via inhibition of both metastatic cancer cells and immunosuppressive myeloid cells in the TME.